Governing alongside: Lateral state spatiality and unmet expectations amid mining negotiations in Casamance, Senegal. (11th January 2019) - FENT, ASHLEY
ABSTRACT: Since 2014, local and regional state administrators in Senegal have negotiated a controversial zircon and titanium sands mining venture in villages of the Casamance region. Positioning themselves "alongside" the population, they enacted a lateral spatiality of the state by organizing opportunities for dialogue, drawing on fictive kinship relations, and articulating a governmental approach of "accompaniment, " which focused on collaborating with local people. Yet residents of Niafarang and nearby villages wanted an idealized version of the state that would deliver benefits and protection from the top down, and they were frustrated by the Senegalese state's self‐interest. As the debate continued, administrators used vertical authority to secure local acceptance of the mining project. Lateral relations therefore both challenged and bolstered vertical state power over localities, illustrating the multiple, conflicting spatialities of state practice. [ mining, development, state spatiality, expectations of the state, Casamance, Senegal ] Abstract : A tree‐planting event near Niafarang, Senegal, in September 2015, attended by local residents and state agents working for the Marine Protected Area of Abéné.